Comiss\~oes parlamentares e os conflitos entre executivo e legislativo em torno da política econômica no Brasil contemporâneo - Fabiano Santos; Salvador Teixeira Werneck Vianna; Yago Paiva; Beatriz Rey (Instituto de Pesquisa Econômica Aplicada (IPEA), 2024)
– The study examines the extent to which the Legislative Branch is involved in the processing of economic policies sent by the Executive Branch, as part of the process of political delegation. It argues that, as the PT administrations adopted a developmentalist economic paradigm, increasing the distance of preferences from the other members of the coalitions, the Executive sought to transform delegation into abdication. The Legislative branch is expected to react by increasing the levels of intra-coalition conflicts. In order to test these hypotheses, we examined whether the PT governments attempted to control the economic affairs committees and whether they actually sent more developmentalist proposals. With regard to the Legislative, we checked whether members of the coalitions reacted by trying to amend more of the Executive's bills and whether the success rate of the governments in turning bills into law decreased. To do this, we assessed economic legislation submitted by the Executive to the Finance and Taxation Committee (CFT) and the Economic Development, Industry, Trade and Services Committee (CDeics). The results corroborate our hypotheses, demonstrating that the Legislative challenges more developmental economic policies.
Keywords: E02; H11; H77; 330; economic policy; Executive; Legislative; delegation; coalition presidentialism